Drosophila Brakeless Interacts with Atrophin and Is Required for Tailless-Mediated Transcriptional Repression in Early Embryos - Haecker, Achim (Public Library of Science, 2007)
Complex gene expression patterns in animal development are generated by the interplay of transcriptional activators and repressors at cis-regulatory DNA modules (CRMs). How repressors work is not well understood, but often involves interactions with co-repressors. We isolated mutations in the brakeless gene in a screen for maternal factors affecting segmentation of the Drosophila embryo. Brakeless, also known as Scribbler, or Master of thickveins, is a nuclear protein of unknown function. In brakeless embryos, we noted an expanded expression pattern of the Krüppel (Kr) and knirps (kni) genes. We found that Tailless-mediated repression of kni expression is impaired in brakeless mutants. Tailless and Brakeless bind each other in vitro and interact genetically. Brakeless is recruited to the Kr and kni CRMs, and represses transcription when tethered to DNA. This suggests that Brakeless is a novel co-repressor. Orphan nuclear receptors of the Tailless type also interact with Atrophin co-repressors. We show that both Drosophila and human Brakeless and Atrophin interact in vitro, and propose that they act together as a co-repressor complex in many developmental contexts. We discuss the possibility that human Brakeless homologs may influence the toxicity of polyglutamine-expanded Atrophin-1, which causes the human neurodegenerative disease dentatorubral-pallidoluysian atrophy (DRPLA).